Enhancing mode I inter-laminar fracture toughness of aluminum/fiberglass fiber-metal laminates by combining surface pre-treatments. (October 2017) - Laban, O.; Mahdi, E.
Abstract: This paper investigates the influence of multiple surface treatment, including chemical etching and plasma treatments, on the mode I inter-laminar fracture toughness ( G 1 C ) of aluminum/fiberglass fiber-metal laminates. Laser technology was employed to further enhance aluminum substrate surface morphology to promote micro-mechanical interlocks (MMI) with non-crimp [0°/−45°/90°/+45°] fiberglass/epoxy resin. A vacuum assisted resin transfer molding technique was used to produce the hybrid laminates. Five surface pre-treatments were compared; N2 plasma, O2 plasma, alkaline etch, laser, and laser+N2 plasma. Alkaline etched specimens absorbed the highest energy (237.8%) whereas laser+N2 plasma treated specimens exhibited the highest G 1 C (73.2%). In addition, when MMI is promoted, the mechanical locks acted as localized obstacles resisting the propagating crack and caused transition of failure mode from adhesive to adhesive-cohesive mixed mode.